Pembelajaran Cinta Lingkungan Berbasis Sistem Merdeka Untuk Membentuk Profil Pancasila Siswa PAUD - Salis Irvan Fuadi; nur farida (Muróbbî: Jurnal Ilmu Pendidikan, 2022)
The purpose of this study was to determine the process of developing a learning model for environmental love based on an independent system to form a Pancasila profile (Gotong-Royong, Critical and Creative Reasoning) for early childhood. The long-term goal of this research is to provide information and recommendations regarding the application of the Independent System-Based Environmental Love Learning to Form a Pancasila Profile. This research was carried out with a Research and Development design that adopted the Borg & Gall model. The quantitative method is carried out by measuring using a Likert Scale questionnaire with 4 (Four) Standards and the respondents are students, filling is assisted and accompanied by a teacher assistant. Qualitative method using observation sheets and questionnaires that aim to be used to ensure that the process of implementing learning is in accordance with the syntax of the learning model and efforts to obtain information on needs and input from teachers and observers to improve the application of the model.